2012
DOI: 10.1071/wf10079
|View full text |Cite
|
Sign up to set email alerts
|

The influence of prescribed fire on the extent of wildfire in savanna landscapes of western Arnhem Land, Australia

Abstract: Fire regimes in many north Australian savanna regions are today characterised by frequent wildfires occurring in the latter part of the 7-month dry season. A fire management program instigated from 2005 over 24 000 km2 of biodiversity-rich Western Arnhem Land aims to reduce the area and severity of late dry-season fires, and associated greenhouse gas emissions, through targeted early dry-season prescribed burning. This study used fire history mapping derived mostly from Landsat imagery over the period 1990-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 42 publications
(43 reference statements)
2
50
0
Order By: Relevance
“…Many studies have also argued that implementing a prescribed EDS burning program has substantial benefits in restricting the spread of extensive LDS wildfires (e.g. Russell-Smith et al 1997, 2003Yates et al 2008;Price et al 2012 Price et al (2012) showed that mean fire extent in the LDS period was reduced by 16.5% by comparison with the mean extent for the prior 15 years, yielding a mean overall reduction of 6%. Reduction in the extent and severity of LDS fires is known to have significant benefits both for obligate seeders and resprouting species (Williams et al , 1999Russell-Smith et al 2002b.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have also argued that implementing a prescribed EDS burning program has substantial benefits in restricting the spread of extensive LDS wildfires (e.g. Russell-Smith et al 1997, 2003Yates et al 2008;Price et al 2012 Price et al (2012) showed that mean fire extent in the LDS period was reduced by 16.5% by comparison with the mean extent for the prior 15 years, yielding a mean overall reduction of 6%. Reduction in the extent and severity of LDS fires is known to have significant benefits both for obligate seeders and resprouting species (Williams et al , 1999Russell-Smith et al 2002b.…”
Section: Discussionmentioning
confidence: 99%
“…Leverage varies according to the annual extent of wildfire, extent of fuel treatment and the rate at which fuel loads recover (Price 2012). Leverage has been analysed on individual burns (Loehle 2004) and across landscapes (Boer et al 2009;Price et al 2012;Price et al 2015a). In a bioregional analysis of south-eastern Australia, Price et al (2015b) found no evidence of leverage within the study area's bioregion for the period 1970-2010.…”
Section: Discussionmentioning
confidence: 99%
“…Early dry-season PB succeeded in decreasing the annual burnt fraction of the landscape from 38 to 30 %, especially of late dry-season fires (29 to 12.5 %), as assessed from Landsat imagery for the period of 1990 to 2009, with a burn leverage of 0.9 [56], and cut carbon emissions by 38 % [10]. In the Arnhem Land (56,000 km 2 ), there is a 92 % probability of very large (110 to 2300 km 2 ) fires stopping at the edge of early dry-season fires [57].…”
Section: Landscape-to Regional-scale Studiesmentioning
confidence: 99%